1974
DOI: 10.1172/jci107883
|View full text |Cite
|
Sign up to set email alerts
|

The Central Nervous System as a Site of Action for the Coronary Vasoconstrictor Effect of Digoxin

Abstract: A B S T R A C T Digitalis is known to have a vasoconstrictor effect in the coronary circulation. Recent studies have demonstrated that the coronary vasoconstrictor effects of acetylstrophanthidin and digoxin are neurally mediated via alpha adrenergic fibers. In the present study, experiments were done in 20 dogs anesthetized with chloralose and urethane to study the central nervous system as a possible site of action for this vasoconstrictor effect of digoxin. After the intravenous administration of 1.0 mg dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 22 publications
(23 reference statements)
1
20
0
Order By: Relevance
“…Recently, Garan et al (1974) determined the CSF and plasma concentrations of digoxin following intravenous injection. They found that the highest CSF value was 2.3 ng/ml (2.9 pmol/ml) with a CSF/plasma ratio of about 0.05.…”
Section: Ionic Composition Ofplasma and Csf As Affected By Arrhythmogmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Garan et al (1974) determined the CSF and plasma concentrations of digoxin following intravenous injection. They found that the highest CSF value was 2.3 ng/ml (2.9 pmol/ml) with a CSF/plasma ratio of about 0.05.…”
Section: Ionic Composition Ofplasma and Csf As Affected By Arrhythmogmentioning
confidence: 99%
“…By simultaneously recording sympathetic and phrenic nerve activity together with the ECG, the above workers demonstrated a relationship between the enhanced neuronal activity and cardiac disorders following systemic injection of digitalis. We felt that these studies of Gillis (1969) and recent claims of Garan, Smith & Powell (1974) were sufficiently impressive to require careful evaluation of the CNS as a possible site of digitalis-induced dysrhythmia. Thus, we undertook a systematic evaluation to determine: (1) the rate of appearance of systemically administered cardiac glycosides, namely ouabain and digitoxin, in the cerebrospinal fluid (CSF); (2) the uptake of these cardiac glycosides in various brain areas; and (3) the effect of these cardiac glycosides upon the ionic composition of the CSF.…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3 and our previous work (9)(10)(11). The work by Garan et al (12) suggests that the central nervous system is the site of action of the increase in arterial resistance after digitalis administration. The alpha adrenergically mediated increase in transhepatic resistance with ouabain may also be mediated through the central nervous system, although, recently published data by Lorenz et al (13) suggest that ouabain may release norepinephrine from neuronal stores in isolated venous segments.…”
Section: Discussionmentioning
confidence: 51%
“…Twenty-two male subjects (age 22±t1 year, mean+SEM) were studied in three treatment groups: digitalis group (n=8; subjects 1-8), dobutamine group (n=8; subjects [9][10][11][12][13][14][15][16], and placebo group (n=6; subjects [17][18][19][20][21][22]. All subjects were studied without sedation in the supine, postabsorptive state and were free of cardiovascular or other systemic diseases based on medical history and physical examination.…”
Section: Subjectsmentioning
confidence: 99%